Genotoxic risk in humans and acute toxicity in rats of a novel oral high-dose coenzyme Q10 oleogel. (2021) - Masotta, Natalia Ehrenhaus; Martinez-Perafan, Fabian; Carballo, Marta Ana; Gorzalczany, Susana Beatriz; Rojas, Ana M.; Tripodi, Valeria P.
Graphical abstract: Highlights: An oral high-dose CoQ10 oleogel was assessed in its genotoxicity and acute toxicity. There was no genotoxic risk associated with the use of CoQ10 oleogel in volunteers. Biochemical parameters remained within reference values after oleogel treatment. No signs of toxicity or mortality were observed in the rats exposed to the oleogel. The novel high-dose CoQ10 oleogel formulation designed is safe for oral consumption. Abstract: Coenzyme Q10 (CoQ10 ) supplementation has demonstrated to be safe and effective in primary and secondary CoQ10 deficiencies. Previously, we have designed a high-dose CoQ10 oleogel (1 g/disk) with excipients used in quantities that do not represent any toxic risk. However, it was necessary to demonstrate their safety in the final formulation. Following this purpose, an acute toxicity study of the oleogel in rats was performed. Furthermore, the genotoxic risk was evaluated in human volunteers after CoQ10 supplementation with oleogel and compared to the solid form (1 g/three 00-size-capsules). In addition, the general health status and possible biochemical changes of the participants were determined using serum parameters. Results suggested the absence of adverse effects caused by the interaction of the components in the oleogel formulation. Therefore, we conclude that the designed novel high-dose CoQ10 oleogel was safe for oral consumption.